2024
DOI: 10.1136/archdischild-2023-326500
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines for children and adolescents experiencing gender dysphoria or incongruence: a systematic review of recommendations (part 2)

Jo Taylor,
Ruth Hall,
Claire Heathcote
et al.

Abstract: BackgroundIncreasing numbers of children and adolescents experiencing gender dysphoria/incongruence are being referred to specialist gender services and there are various published guidelines outlining approaches to clinical care.AimTo examine the recommendations about the management of children and/or adolescents (age 0-18) experiencing gender dysphoria/incongruence in published guidelines or clinical guidance. A separate paper examines the quality and development of guidelines.MethodsA systematic review and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, its reliability in this context may be questionable since several other systematic reviews have applied this tool to some of the same studies and arrived at quite different conclusions, with some also criticising the usefulness of AGREE-II for GAC guidelines. [22][23][24] Notably, the most restrictive guidelines were rated highest in this systematic review, without a clear justification related to how these guidelines were developed, 6,25 while guidelines for more affirmative models of care were judged to be of higher quality in other reviews than by Taylor and colleagues. [22][23][24] An adapted version of the Newcastle-Ottawa Quality Assessment Scale 26 (NOS) was used in three of the systematics instead of the MMAT 2,3,7 -a deviation from the protocol that was not explained or clearly reported.…”
Section: Domain 3: Data Collection and Study Appraisalmentioning
confidence: 70%
See 1 more Smart Citation
“…However, its reliability in this context may be questionable since several other systematic reviews have applied this tool to some of the same studies and arrived at quite different conclusions, with some also criticising the usefulness of AGREE-II for GAC guidelines. [22][23][24] Notably, the most restrictive guidelines were rated highest in this systematic review, without a clear justification related to how these guidelines were developed, 6,25 while guidelines for more affirmative models of care were judged to be of higher quality in other reviews than by Taylor and colleagues. [22][23][24] An adapted version of the Newcastle-Ottawa Quality Assessment Scale 26 (NOS) was used in three of the systematics instead of the MMAT 2,3,7 -a deviation from the protocol that was not explained or clearly reported.…”
Section: Domain 3: Data Collection and Study Appraisalmentioning
confidence: 70%
“…Seven systematic reviews were commissioned by the Cass Report and published in the BMJ Archives of Disease in Childhood [2][3][4][5][6][7][8] with a single systematic review protocol registered in PROSPERO for all seven reviews 9 . To evaluate their risk of bias we applied the ROBIS tool 10 as recommended by Cochrane 11,12 .…”
Section: The Systematic Reviewsmentioning
confidence: 99%
“…The research carried out by York University, published in the Archives of Disease in Childhood , found that the evidence on the use of puberty blockers and hormones in young people with gender related distress was wholly inadequate, making it impossible to gauge their effectiveness or their effects on mental and physical health 4567. “No conclusions can be drawn about the impact on gender dysphoria, mental and psychosocial health, or cognitive development,” the research concluded.…”
mentioning
confidence: 99%
“…That verdict is supported by a series of review papers published in Archives of Disease in Childhood , a journal published by BMJ and the Royal College of Paediatrics and Child Health (doi:10.1136/archdischild-2023-326669 doi:10.1136/archdischild-2023-326670 doi:10.1136/archdischild-2023-326499 doi:10.1136/archdischild-2023-326500). 3456 The evidence base for interventions in gender medicine is threadbare, whichever research question you wish to consider—from social transition to hormone treatment.…”
mentioning
confidence: 99%